Crank eaudiobook - Hopkins, Ellen (HighBridge Audio, 2008)
Kristina Georgia Snow is the perfect daughter: gifted high school junior, quiet, never any trouble. But on a trip to visit her absentee father, she meets a boy who introduces her to crank. At first she finds it freeing, but soon Kristina's personality disappears inside the drug. What began as a wild, ecstatic ride turns into a struggle through hell for her mind, her soul, and her life.